2022
DOI: 10.1515/nanoph-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

VO2 metasurface smart thermal emitter with high visual transparency for passive radiative cooling regulation in space and terrestrial applications

Abstract: Smart radiative cooling devices based on thermochromic materials such as vanadium dioxide (VO2) are of practical interest for temperature regulation and artificial homeostasis, i.e., maintaining stable equilibrium conditions for survival, both in terrestrial and space applications. In traditional solar reflector configurations, solar absorption in the VO2 layer is a performance limiting factor due to the multiple reflections of sunlight in the stack. Here, we demonstrate a visually transparent, smart radiator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 71 publications
0
38
0
Order By: Relevance
“…(ALD). [29][30][31][32][33] Among these techniques, ALD stands out as a deposition technique compatible with CMOS technology and large-area mass production. In particular, Peter et al demonstrated that a sub-10 nm VO 2 continuous film can be formed on 300 mm diameter Si substrates with a clear transition capability in electrical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ALD). [29][30][31][32][33] Among these techniques, ALD stands out as a deposition technique compatible with CMOS technology and large-area mass production. In particular, Peter et al demonstrated that a sub-10 nm VO 2 continuous film can be formed on 300 mm diameter Si substrates with a clear transition capability in electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…VO 2 films have been synthesized by a wide range of deposition techniques, such as pulsed laser deposition, [ 25 ] sol‐gel processing, [ 26 ] reactive sputtering, [ 4,27 ] epitaxy, [ 28 ] and atomic layer deposition (ALD). [ 29–33 ] Among these techniques, ALD stands out as a deposition technique compatible with CMOS technology and large‐area mass production. In particular, Peter et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36,37 ] Nevertheless, most daytime radiative cooling technologies do not consider lighting and esthetic purposes and cannot be applied to objects such as the windows and glass curtain walls of buildings and vehicles. [ 38–42 ] Conventional windows (particularly skylights) in vehicles and buildings transmit almost 90% of the total incident solar radiation [ 43–45 ] and demonstrate significant heat transfer with outdoor air, whose temperature is beyond 36 °C in tropical weather, which consequently significantly increases the energy expenditure of refrigeration systems. Approximately 20% of the entire energy consumption in buildings can be attributed to stick‐in‐the‐mud windows, [ 46,47 ] and over 30% of the total energy in vehicles is lost through windows.…”
Section: Introductionmentioning
confidence: 99%
“…[36,37] Nevertheless, most daytime radiative cooling technologies do not consider lighting and esthetic purposes and cannot be applied to objects such as the windows and glass curtain walls of buildings and vehicles. [38][39][40][41][42] Conventional windows (particularly skylights) in vehicles and buildings transmit almost 90% of the total incident solar radiation [43][44][45] Common glass without spectral regulation effect cannot offer an energy-saving function, and radiative cooling technology without visible transparency cannot satisfy the illumination and esthetic demands. Herein, the concept of utilizing a biomimetic beetle cuticle structure, guided by principles of Chinese Taoist philosophy, is proposed to accomplish efficient radiative regulation.…”
mentioning
confidence: 99%
“…Landy et al proposed a metamaterial that can efficiently absorb electromagnetic radiation, with a wide absorption bandwidth and polarization insensitivity [10]. These absorbers achieving high absorption of light can effectively convert solar energy into heat energy, which is important for utilizing solar energy for people [11][12][13][14][15]. In addition, the absorbers based on meta-materials and surface plasmon materials have significant application in a variety of multispectral applications, such as photon detection, spectrum sensing, photocatalysis, etc.…”
Section: Introductionmentioning
confidence: 99%